KOLABORASI HIDDEN CURRICULUM DALAM PENGUATAN PENDIDIKAN KARAKTER LINGKUNGAN SEKOLAH - Muhammad Fauzi (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2019)
The education curriculum consists of formal, informal and non-formal curriculum. Formal curriculum includes activities in the classroom and is planned, non-formal curriculum consists of activities that are also planned but not directly related to academic learning in class, and the existence of this curriculum is seen as a supplement (supplement) formal curriculum. Besides these curricula, there is also a hidden curriculum. Hidden curriculum is a curriculum that is not studied, curriculum that is not planned programmatically but whose presence has a major influence on changes in student behavior in the learning process. Character education is part of the hidden curriculum in the learning process in the school environment that is not written directly in the official school curriculum. The strengthening of character education summarized in the hidden curriculum of the school has several main character values, as mentioned by the Ministry of Education and Culture there are 18 namely religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the motherland , appreciate achievement, be friendly / communicative, love peace, love to read, care about the environment, care about social, and responsibility